THE ROLE OF TEACHERS IN EFFECTIVE ONLINE ENGLISH LANGUAGE LEARNING - Saloxiddinov Manuchehr; Zubaydova Nilufar Nematullayevna; A’zamova Gulida Aliyevna (Ustozlar uchun, 2025)
This article explores the role of teachers in effective online English language teaching. It examines the unique characteristics of online education and how they influence teaching methods. The study highlights the shift in teachers’ responsibilities from traditional instructors to facilitators, motivators, and technological guides. Various interactive and student-centered teaching methods are analyzed to enhance language acquisition in a digital environment. The paper also discusses the importance of using technology, multimedia resources, and personalized approaches to improve engagement. Additionally, it addresses the challenges teachers face in virtual classrooms and suggests strategies to overcome them. The findings emphasize that a well-prepared teacher plays a crucial role in ensuring the success of online English language learning.